Nowcasting and forecasting aquaponics by Google Trends in European countries - Dos Santos, Maria José Palma Lampreia (2017)
Aquaponics represents nowadays an innovation in agricultural systems of production and supply food which combines aquaculture fish production with hydroponic production of vegetables, that can contribute to feed an increasing population at the world level, with less inputs in a sustainable way of production and supply. Nowadays in Europe the first commercial firms on aquaponics are taking the first steps. But the majority of the European aquaponics systems are mainly for research and educational purposes. The current institutional European framework, the gaps in legislation and the lack of legislative uniformity among EU Member States (EU MS) have strong negative impacts and hinder commercialization of aquaponics at the European level. The main difficulties include constraints at three different levels: (1) administrative and organizational; (2) technical; and (3) environmental. Major administrative and organizational constraints in the EU MS include that the European standard classification of productive economic activities does not have a general or specific code for aquaponics but only separate codes for animal or plant production. That imply difficulties on accessing the funds from the Europe 2020; (mainly Common Agricultural Policy (CAP)) and the different classification of programs among European MS. Environmental constraints occur due to EU MS environmental legislation, which considers separation of the effluents of aquaponics for plants and for animal production. Solid fish excrements are currently considered fish waste and not plant nutrient. This is another restriction that aquaponics farmers in Europe face and it contributes to a loss of efficiency in the activity. Technical restrictions occur because commercialization and food safety norms are not explicit for aquaponics products. It is therefore difficult to run a business and commercialize the final production because each production type in the cycle belongs to different quality control services at different ministries, depending on the EU. On the opposite way, in United States of America (USA) aquaponics vegetable production is certified as organic production and sell with an increasing value. So, in USA aquaponics production and commercial firms presents a high development across USA. On the other hand, in Middle East countries and Gulf countries present, as well as, USA an increasing interest and development due the scarce resources of water and land.